DE LA TEORIA A LA PRAXIS. LA FISICA DESDE EL PIZARRON, EL LABORATORIO Y EL COMPUTADOR, DIRIGIDO A TECNOLOGOS EN SISTEMATIZACION DE DATOS - CRISTIAN AGUIRRE; HARLEY ORJUELA (Universidad Distrital Francisco José de Caldas, 2010)
The physical sciences have been, are and will be a major conceptual pillars and applications that an engineer and/or technologist must take their knowledge and in their professional practice, because contributes to the development of his thought and in the structure his mind, and here is where the teacher should be a guide to built next to the student the same solid foundations of a man Science, of course, from the classroom with different tools developed.